Science World [motion pictures] Space science : the Solar System; - the sun and its energy; - beyond the solar system. - Coronet (Northbrook, IL Coronet/MTI Film and Video, 1989)
Science World ... journeys from depths of the ocean to the outer reaches of the galaxy. Spectacular photography in award-winning programs expolres the basic framework of our world.
Vol. 18: The Solar System; - The sun and its energy; - Beyond the solar system
Original copy in VHS format (VHS 18)
[Distributed by] International Book Center, Philippines
Keywords: Sun; Solar System